KARAKTERISTIK SABUN CAIR EKSTRAK BUAH LERAK DENGAN VARIASI KOLAGEN IKAN KOMERSIAL - Maulana, Ripky; Rahmawati, Hafni; Agustiana, Agustiana (Fish Scientiae, 2025)
Liquid soap is widely favored for its practicality and ease of use, making it a popular personal care product. Fish collagen is well-known for its ability to improve skin hydration and texture, while soapnut fruit (lerak) serves as a natural cleansing agent due to its high saponin content. This study evaluated liquid soap formulations containing different concentrations of commercial fish collagen (1%, 3%, and 5%) using a completely randomized design (CRD). The parameters assessed included viscosity, pH, total plate count (TPC), and organoleptic properties (color, aroma, and consistency). The results indicated that increasing collagen concentrations led to a significant rise in viscosity, with the 1% collagen formulation (treatment A) achieving an optimal viscosity of 1650 mPa·s, which complies with liquid soap standards. All formulations maintained pH levels within the acceptable range of 8–11 and met microbiological safety standards based on TPC analysis. Organoleptically, treatment A was rated the highest, featuring a visually appealing light grey color, a pleasant virgin coconut oil aroma, and a suitable consistency. Overall, the 1% collagen formulation (treatment A) was identified as the optimal formula, meeting the requirements of the Indonesian National Standard for liquid soap (SNI 06-4085-1996).